Modelling of fusion zone formation in shielded metal arc welding; Structural Integrity and Life; Vol. 20, № 3 - Ivanov V. P. Vitaly Petrovich; Lavrova E. V. Elena Vladimirovna; Ilyashchenko D. P. Dmitry Pavlovich; Verkhoturova E. V. Elena Viktorovna (2020, 2020)
Title screen